Educação na Casa Familiar Rural de Capanema/PR: práticas educativas de educação rural ou educação do campo? - Silva, Felipe Alexandre da (2015)
It s notorious that the Brazilian countryside is rooted in a historical process of worker exploration and submission of its subjects. Therefore, the offered education to those subjects presented countless pedagogical discrepancies and social dissonances, especially until the end of the XX century when the Countryside Education was constituted in Brazil. This model of education emerged from concerns and struggles of social movements towards the inadequate pedagogical practices adopted to the countryside subjects. However, even with the state s acceptance in relation to these measures achieved through intense and continuous struggles of the social movements it still cannot be stated that the Countryside Education is present in every educational institution, even those that call themselves as members of this pedagogical model. So from readings, reflections and data collected in fieldwork in the year of 2014 -, the present work has intuit to ascertain if the Rural Family House located in Capanema/PR follows the precepts of the Rural Education or the Countryside Education both in its theories and in pedagogical practices.